Aromaticity and antiaromaticity in the excited states of porphyrin nanorings - Peeks, M; Gong, J; McLoughlin, K; Kobatake, T; Haver, R; Herz, L; Anderson, H (American Chemical Society, 2019)
Aromaticity can be a useful concept for predicting the behavior of excited states. Here we show that π-conjugated porphyrin nanorings exhibit size-dependent excited-state global aromaticity and antiaromaticity for rings containing up to eight porphyrin subunits, although they have no significant global aromaticity in their neutral singlet ground states. Applying Baird's rule, even rings ([4 n] π-electrons) are aromatic in their lowest excited states, whereas the lowest excited states of odd rings ([4 n + 2] π-electrons) are antiaromatic. These predictions are borne out by density functional theory (DFT) studies of the nucleus-independent chemical shift (NICS) in the T1 triplet state of each ring, which reveal the critical importance of the triplet delocalization to the emergence of excited-state aromaticity. The singlet excited states (S1) are explored by measurements of the radiative rate and fluorescence peak wavelength, revealing a subtle odd-even alternation as a function of ring size, consistent with symmetry breaking in antiaromatic excited states.